2021
DOI: 10.3390/w13182598
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of Cr(III) from Tannery Effluents by Diafiltration Using Chitosan Modified Membranes

Abstract: The selective recovery of chromium remaining in tannery effluents after the leather tanning process is highly desirable to potentiate its reuse, simultaneously minimizing the ecotoxicity of these effluents. To the best of our knowledge, this work evaluates for the first time the ability of a chitosan-based membrane for selective recovery of chromium from a tannery wastewater by subsequent diafiltration and selective chromium desorption, envisaging their integration after tannery wastewater treatment by reverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…The elevated chitosan's affinity to heavy metals attracts additional attention in developing chitosan-based membranes for eliminating such metals from wastewater, benefitting from both their adsorptive and water filtration abilities. The literature review shows that Chitin is more protonated at low pH and at this pH, it is apt to retain anions through electrostatic attraction [15][16][17][18][19]. To the best of our knowledge, this is the first time in which adsorption of Co from synthetic wastewater is performed using Chitin.…”
Section: Introductionmentioning
confidence: 93%
“…The elevated chitosan's affinity to heavy metals attracts additional attention in developing chitosan-based membranes for eliminating such metals from wastewater, benefitting from both their adsorptive and water filtration abilities. The literature review shows that Chitin is more protonated at low pH and at this pH, it is apt to retain anions through electrostatic attraction [15][16][17][18][19]. To the best of our knowledge, this is the first time in which adsorption of Co from synthetic wastewater is performed using Chitin.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, Zakmout et al [64] suggested a two-step process for the recovery of chromium (III) from tannery effluents based on a preliminary concentration of these effluents by RO, followed by treatment with a chitosan-based membrane. Real and synthetic effluents were previously concentrated by using an SW30 RO membrane (DOW Chemical Company Midland, MI, USA) which rejected more than 99% of chromium allowing for the production of a permeate stream meeting the requirements for direct discharge into natural environments.…”
Section: Recovery Of Chromium Saltsmentioning
confidence: 99%
“…The number of bed volumes (BV) is the ratio between the volume of the adsorbate solution and the amount of adsorbent used [63]. The two parameters are commonly used to compare the ability of different adsorbents to remove a specific impurity from the influent [64].…”
Section: Fixed-bed Studiesmentioning
confidence: 99%